2018
DOI: 10.1371/journal.pone.0193392
|View full text |Cite
|
Sign up to set email alerts
|

An anti-PDGFRβ aptamer for selective delivery of small therapeutic peptide to cardiac cells

Abstract: Small therapeutic peptides represent a promising field for the treatment of pathologies such as cardiac diseases. However, the lack of proper target-selective carriers hampers their translation towards a potential clinical application. Aptamers are cell-specific carriers that bind with high affinity to their specific target. However, some limitations on their conjugation to small peptides and the functionality of the resulting aptamer-peptide chimera exist. Here, we generated a novel aptamer-peptide chimera th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Recently, we reported the use of GL21.T and Gint4.T aptamers as carriers for miR-137 and anti-miR-10b to target GSCs. Both bind Axl and PDGFRβ,21, 25, 26 respectively, two tyrosine kinase receptors commonly expressed on GBM cells. These aptamers bind to targets shared between stem and differentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported the use of GL21.T and Gint4.T aptamers as carriers for miR-137 and anti-miR-10b to target GSCs. Both bind Axl and PDGFRβ,21, 25, 26 respectively, two tyrosine kinase receptors commonly expressed on GBM cells. These aptamers bind to targets shared between stem and differentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent report, Sullenger and colleagues modified RNA aptamers against prostate cancer cells with 2′F pyrimidines. Upon conjugation with small molecule drugs or therapeutic peptides, these aptamers displayed significant specificity and toxicity against cancerous but not normal cells [ 196 , 197 ]. We direct the reader to a recent review for a more detailed panorama of modified aptamer chemistry and related technologies [ 198 ].…”
Section: Non-natural Nucleic Acids For Therapeutic Applicationsmentioning
confidence: 99%
“…Recently Romanelli et al [ 43 ] developed a peptide (R7W-MP) that, by targeting Cavβ2, demonstrated to be able to correct the L-type calcium channel (LTCC) density at the plasma membrane, often hampered in various cardiovascular pathological conditions. The R7W-MP peptide is a fusion molecule composed by a R7W CPP fused to a mimetic peptide (MP), able to target the Tail Interacting Domain (TID) in the Cavβ2, inhibiting its interaction with the C-terminal coiled-coil tail (C-tail) in the site where Cavβ2 is phosphorylated by Akt, and thus, preventing Cavβ2 structural rearrangements responsible for increased LTCC density at the plasma membrane.…”
Section: Aptamer-peptide Conjugatesmentioning
confidence: 99%
“…The R7W-MP peptide revealed to be able to reestablish normal calcium balance and recover myocardial contractility in mouse models of diabetic cardiomyopathy [ 44 ]. In order to overcome limitations showed by the R7W-MP peptide, essentially in reference to the lack of selectivity of the R7W moiety, the same group developed an aptamer-based approach for the selective delivery of MP mimetic to cardiac cells [ 43 ]. The authors described an innovative approach for direct conjugation of the MP to a 2′-fluoro pyrimidines modified RNA aptamer, named Gint4.T, specifically targeting the PDGFRβ that is abundantly expressed in cardiomyocytes [ 45 ].…”
Section: Aptamer-peptide Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation